The Association of Sjögren Syndrome and Autoimmune Thyroid Disorders - Baldini, Chiara; Ferro, Francesco; Mosca, Marta; Fallahi, Poupak; Antonelli, Alessandro (Frontiers in Endocrinology, 2018)
Sjögren’s syndrome (SS) and autoimmune thyroid diseases (AITD) may frequently coexist in clinical practice, resulting in a complex overlapping disorder that represents a particular example of the expression of heterogeneity in patients with autoimmune diseases. Objective of this review was to describe the prevalence of the SS-AITD association in the most recent literature, exploring in particular to what extent the presence of AITD might influence the clinical expression of SS and vice versa. Moreover, we summarized some of the proposed genetic, biologic and molecular mechanisms implied in the pathogenesis of AITD-SS association. Finally, we explored risk factors for lymphoma development in both AITD and SS. We performed a Medline search of English language articles published in the PubMed database in order to provide a critical overview of the recent literature on pathogenesis and clinical features of AITD-SS overlapping disease.